2020
DOI: 10.1108/jpbm-10-2019-2621
|View full text |Cite
|
Sign up to set email alerts
|

I can’t stop hating you: an anti-brand-community perspective on apple brand hate

Abstract: Purpose This paper aims to the literature on negative consumer-brand relationships by advancing knowledge on the key triggers of brand hate of global and prominent brands. It investigates for the first time the role of brand in triggering brand hate, as well as behavioral and emotional brand hate outcomes, i.e. willingness to punish and negative brand engagement. Additionally, it explores the impact of product ownership and previous love feelings in the formation of brand hate. Design/methodology/approach Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 146 publications
2
76
0
Order By: Relevance
“…On similar lines of research, Rodrigues et al. (2020) found that due to negative brand experiences and the inauthentic nature of brands, consumers form anti‐BCs and negatively engage with the brand in the form of brand avoidance spreading negative WOM. Some even investigated the aftereffects and mitigation of negative e‐WOM in the online BCs (Herhausen et al., 2019; Relling et al., 2016).…”
Section: Progression Of Research In the Field Of Bcs (Ro2)mentioning
confidence: 87%
“…On similar lines of research, Rodrigues et al. (2020) found that due to negative brand experiences and the inauthentic nature of brands, consumers form anti‐BCs and negatively engage with the brand in the form of brand avoidance spreading negative WOM. Some even investigated the aftereffects and mitigation of negative e‐WOM in the online BCs (Herhausen et al., 2019; Relling et al., 2016).…”
Section: Progression Of Research In the Field Of Bcs (Ro2)mentioning
confidence: 87%
“…Brand hate is a complex construct, associated with a variety of emotional and behavioral outcomes that can be characterized as cold, cool or hot (Kucuk, 2019). Cold brand hate occurs when the brand is incongruent with the consumer’s identity and is associated with rejection and silent avoidance of the brand (Fetscherin, 2019; Odoom et al , 2019; Rodrigues et al , 2020). Cool brand hate involves a similar distancing from the brand but is characterized by disgust and greater efforts to communicate the rejection of the brand, particularly within close social circles (Kucuk, 2019; Anaza et al , 2021).…”
Section: Brand Hate and Anti-branding Onlinementioning
confidence: 99%
“…Negative reviews tend to be driven by a need to vent, seek justice or warn others after a service failure (Chen and Yuan, 2020; Nam et al , 2020). The brand hate literature also focuses on the role of service failure and negative emotion (Hegner et al , 2017; Rodrigues et al , 2020), but relates these motivations to the creation of anti-brand communities that provide an outlet for highly motivated detractors to form communities dedicated to criticizing a brand (Fetscherin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These initial studies were followed by further in-depth research on brand avoidance (Lee et al, 2009a); brand rejection (Cromie and Ewing, 2009); brand divorce (Sussan et al, 2012); brand aversion (Alba and Lutz, 2013); anti-branding (Johnson et al, 2011); the attachment-aversion model (Park et al, 2013); and more recently, the brand repulsion/attraction phenomenon (Dessart and Cova, 2021). Increasing attention has also been devoted to brand hate (Rodrigues et al, 2021;Bryson et al, 2013;Grégoire et al, 2009;Alba and Lutz, 2013;Fetscherin and Heinrich, 2015;Romani et al, 2015;Kucuk, 2016Kucuk, , 2018Kucuk, , 2019Zarantonello et al, 2018;Hegner et al, 2017;Fetscherin, 2019;Tuhin, 2019).…”
Section: Introductionmentioning
confidence: 99%